A larva of the eteline lutjanid, Randallichthys filamentosus (Pisces: Perciformes), with comments on phylogenetic implications of larval morphology of basal lutjanids - Leis, Jeffrey M. (Zootaxa, 2005)
The only known larva of Randallichthys filamentosus, a 9.7 mm specimen, is characterized by finray counts of D X,11, A III, 9, 50 lateral-line scales, an extremely long and whip-like spine 2 of the dorsal fin (80% body length), and very long first ray of the pelvic fin (74% body length). Like all eteline larvae, it is fully scaled at a small size. Within the Lutjanidae, this larva shares the otherwise unique morphological features of very elongate whiplike dorsal-fin spine and very elongate pelvic-fin ray with some species of the apsiline genus Paracaesio. Evidence from larvae supports Johnson’s hypothesis, based on adult morphology, that the Etelinae and Apsilinae are basal lutjanids. The morphology of lutjanid larvae, however, suggests several hypotheses of relationships within basal lutjanids that differ from those based on adult morphology: that the lutjanid subfamilies Etelinae and Apsilinae form a monophyletic group, that Paracaesio is polyphyletic, that Randallichthys and some Paracaesio spp. are closely related, and that Aphareus is closely related to Pristipomoides, not Randallichthys.